2011
DOI: 10.1016/j.envres.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood lead levels are associated with biomarkers of joint tissue metabolism in African American and white men and women: The Johnston County Osteoarthritis Project

Abstract: Purpose To examine associations between biomarkers of joint tissue metabolism and whole blood lead (Pb), separately for men and women in an African American and Caucasian population, which may reflect an underlying pathology. Methods Participants in the Johnston County Osteoarthritis Project Metals Exposure Sub-study (329 men and 342 women) underwent assessment of whole blood Pb and biochemical biomarkers of joint tissue metabolism. Urinary cross-linked N telopeptide of type I collagen (uNTX-I) and C-telopep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…As reported previously, this well-characterized cohort includesnon-institutionalized individuals, aged 45 years and older,from six selected townships in Johnston County NC (23). The biomarkers sub-study was performed from 2003–2008 on a subset of participants (n=671) selected to represent a balance by gender (50% female) and to include a large proportion of African Americans (37%) (24). Participants with radiographic evidence of rheumatoid arthritis were excluded.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported previously, this well-characterized cohort includesnon-institutionalized individuals, aged 45 years and older,from six selected townships in Johnston County NC (23). The biomarkers sub-study was performed from 2003–2008 on a subset of participants (n=671) selected to represent a balance by gender (50% female) and to include a large proportion of African Americans (37%) (24). Participants with radiographic evidence of rheumatoid arthritis were excluded.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Blood for serum and second morning void urine samples were obtained and then stored at −86°C, as previously reported (24). …”
Section: Participants and Methodsmentioning
confidence: 99%
“…This sub-study was designed to consist of 1700 consecutive individuals from T1* and from the original cohort’s first follow-up (T1) who returned for their second follow-up (T2) in 2006–2008. 29 The sample for the current analysis included participants selected from T1* who had complete biomarker analyses performed (n=555). Urinary CTX-II had missing values for 18 participants and urinary NTX-I had a single participant missing value.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies indicate that exposure to Pb can lead to osteopenia 4,5 , osteoporosis 6 , impaired bone healing 7 , and even osteoarthritis 8e10 . Furthermore, it was shown that whole blood Pb levels are associated with biomarkers of joint tissue metabolism and may play a role in osteoarthritis 11 . Nelson et al found a correlation between elevated blood Pb levels and the incidence of osteoarthritis but question remained if this is the result of a direct toxic effect of Pb on the joint tissue or if Pb is released from the mineralized tissue 12 .…”
Section: Introductionmentioning
confidence: 99%